Effect of mindfulness-based interventions on anxiety, depression, and stress in patients with coronary artery disease: a systematic review and meta-analysis of randomized controlled trials - Abdul Manan, Hanani; Mir, Imtiyaz Ali; Humayra, Syeda; Tee, Rong Yuen; Vasu, Deepak Thazhakkattu (Frontiers in Psychology, 2024)
Background: Coronary artery disease (CAD) and mental illnesses are global contributors of morbidity and mortality. Adopting lifestyle interventions is pivotal in coronary artery disease (CAD) management and prevention to amplify cardiovascular and mental well-being. This study aims to quantify the efficacy effect of mindfulness-based interventions (MBIs) on anxiety, depression and stress in CAD patients. Methods: A systematic review and meta-analysis of randomized controlled trials (RCTs) that studied the effect of MBIs on anxiety, depression and/or stress among CAD patients was conducted by searching 4 electronic databases (PubMed, CENTRAL, Scopus and Science Direct) through December 2023. The risk of bias was assessed using the PEDro tool, and the study outcomes were expressed as standard mean difference at 95% CI. Results were considered statistically significant at p ˂ 0.05. Results: Out of 1838 yielded results, 8 RCTs involving 623 participants with a mean age of 56.96 ± 4.89 met the prespecified eligibility criteria. The pooled results showed a statistically significant and beneficial effect of MBIs on CAD patients' mental health status in regards to anxiety (SMD = -0.83; 95% CI [- 1.19, - 0.46],p < 0.001), depression (SMD = -0.86; 95% CI [- 1.14, - 0.58], p < 0.001), and stress (SMD = -0.69; 95% CI [-1.27, -0.12], p = 0.02). The subgroup sensitivity analyses based on the region (Asia vs Europe) indicated a statistically non-significant subgroup effect of MBIs on anxiety (I 2 = 63.9%, p = 0.10) and depression (I 2 = 25.8%, p = 0.25), and a significant effect on stress (I 2 = 80.0%, p =0.03). Although the methodological quality of the trials was generally satisfactory, all studies lacked allocation concealment and blinding. Additionally, gender imbalances, and inadequate follow-up may have potentially compromised the validity of the trials. Conclusion: MBIs are beneficial for improving CAD patients' anxiety, depression and stress symptoms. Nevertheless, it is imperative to conduct more rigorous and robust studies with an equal gender ratio and long-term follow-up to accurately measure the effectiveness of this intervention.